IPTEKS EDUKASI DALAM PENGAMATAN MELAKUKAN TRANSAKSI PERDAGANGAN KOMODITI BERJANGKA PADA PERUSAHAAN PIALANG PT. VICTORY INTERNATIONAL FUTURES - Watupongoh, Sharon Cornelia; Latjandu, Lady Diana (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
PT. Victory International Futures was established in 2003 as a brokerage company in the world financial market that uses information technology to support its business. Centered in the city of Surabaya in the heart of the Indonesian business city. PT. Victory International Futures is one of the institutions recognized by the Indonesian government. We provide 100% focus on trading via the internet using the "Meta Trader 5" system PT. Victory International Futures is under the supervision of the Commodity Futures Trading (BAPPEBTI), Member of Indonesia Commodity & Derivatives Exchanges (ICDX) / Indonesian Commodity and Derivative Exchange (BKDI) and PT. Identrust Security International (ISI). Time never stops in the era of global trade and so does PT. Victory International Futures serves thousands of customers directly and always provides quality and professional financial services.Keywords : brokerage company, gold, forex, trading system via the internet